Sistema web responsivo para gestão do controle da produção de café - CUNHA, Angélica Angélica Carvaho (2016)
The south region of Minas Gerais stands out nationally for its coffee culture, where most of its producers have family farming characteristics, thus having certain technological need. Considering these aspects, many producers do not have software to carry out the management control of their productions. Information systems have greatly added in various industries, and it would be no different in agribusiness. Thus, it is essential that the lagged technologically farmers can have access to the tools to become more competitive enterprise. Therefore, the aim of this study was to develop web system that aims to coffee production management. Such a system was developed from interviews with coffee farmers in the southern region of Minas Gerais, where ascertained how it is necessary to online systems that auxiliary in the management of properties. To develop the system used the PHP web programming language, JavaScript and MySQL database. It should be noted that the system has the responsive feature, adapting well in different sizes and shapes of devices. The system was developed by the importance of having a friendly interface and easy to use.